Students' Perceptions of JASP Use and Its Impact on Statistics Learning: A TAM-Based Study - A. Muhajir Nasir (EduMa: Mathematics education learning and teaching, 2025)
This study aims to analyze the influence of students' perceptions regarding the use of the JASP application and its relationship to statistics learning outcomes through the Technology Acceptance Model (TAM) approach. The four main TAM constructs analyzed include perceived ease of use, perceived usefulness, attitude toward use, and behavioral intention to use. This research employed a quantitative associative method using simple and multiple linear regression analyses. The sample consisted of 90 fourth-semester PGSD UNM students who had completed a statistics course, selected through simple random sampling. The results indicate that three out of the four perception variables—perceived ease of use, perceived usefulness, and attitude toward use—significantly influenced students’ learning outcomes, with attitude toward use emerging as the strongest predictor. In contrast, behavioral intention to use did not show a significant effect. The multiple regression model revealed that the four TAM constructs collectively explained 55.7% of the variance in learning outcomes. These findings affirm that students’ positive perceptions of JASP have a tangible impact on academic achievement and support the effectiveness of the application as a learning tool for statistics in the PGSD context.